THE ROLE OF DIGITAL LEADERSHIP IN IMPLEMENTING THE GREEN TALENT MANAGEMENT IN THE DIGITAL ERA - K.P.Suharyono S.Hadiningrat; Febri Pramudya Wardani Febri; Verry Albert Jekson Mardame Silalahi; Fikri Achmad Abdullah Febri (JIPOWER : Journal of Intellectual Power, 2025)
Digital leadership plays a central role in implementing Green Talent Management (GTM) in the digital age, particularly in the Indonesian context. Given significant challenges such as the lack of electricity and internet infrastructure in approximately 2,500 villages, the role of digital leadership is crucial in bridging this gap. This article analyzes global and national conditions related to GTM, demonstrating how digital skills and sustainability integrate to enhance workforce competitiveness. The research method employed descriptive qualitative research with a thematic narrative approach to illustrate the role of digital leadership in implementing GTM in the digital age. It found that adaptive and innovative digital leadership is capable of advocating for digital infrastructure development, creating alternative solutions, and empowering local communities through technology-based training. Recommendations are generated for global and national leadership, including the need for international collaboration, investment in infrastructure development, and efforts to empower communities with relevant education. Thus, this article contributes to a better understanding of the role of digital leadership in addressing the challenges of sustainability and digital transformation in Indonesia.